Modele wewnętrzne w ocenie działalności zakładów ubezpieczeń - Kurek, Robert (Internal Models in Evaluation of Activity of Insurance Companies, 2008)
The article presents the idea of applying internal models in evaluation of activity of insurance companies. These issues have been additionally explored due to presentation of risks that should appear in the model regardless of the mean of communication following from them. They include technical and insurance risk as well as assets and operational risks. Moreover, both the inside and outside organizational circumstances of applying the models have been presented together with advantages and obstacles resulting from applying the internal models by insurance companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 82-90